CAREER PROGRESSION, WORK MOTIVATION AND LEADERSHIP STYLES AS FACTORS AFFECTING JOB SATISFACTION OF LIBRARY PERSONNEL IN THE FEDERAL CIVIL SERVICE OF NIGERIA (2014)
Library personnel are at the centre of information provision in the Federal Civil Service of Nigeria for policy formulation and implementation of government programmes and projects. As a result of limited vacancies for career progression (promotion from grade level 07-17), leadership styles (bureaucratic, autocratic and laissez-faire) and poor working conditions, the job satgisfaction of the library personnel has generated much concern. Several studies have focused on work motivation, leadership styles and job satisfaction in organisations but attention has not been paid to the factors of career progression, work motivation and leadership styles of library personnel in the Federal Civil Service of Nigeria. This study, therefore, investigated career progression, work motivation and leadership styles as factors affecting the job satisfaction of library personnel in the Federal Civil Service of Nigeria. The survey research design of correlation type was adopted. Total enumeration method was used to cover all the 450 library personnel in 29 federal ministries and 44 extra-ministerial departments. Four research instruments were used for data collection: Career Progression Questionnaire (r = 0.83), Job Satisfaction Questionnaire (r = 0.85), Work Motivation Questionnaire (r = 0.94) and Leadership Styles Questionnaire (r = 0.81). A total of 426 copies of the questionnaire were completed and returned. The response rate achieved was 94.7%. Five research questions were answered and four hypotheses tested at 0.05 level of significance. Data were analysed using Pearson Product Moment Correlation and Multiple Regression Analysis. Results showed significant relationships between the independent variables and the dependent variable as follows: career progression and job satisfaction (r = 0.46, p<0.05); work motivation and job satisfaction (r = 0.11, p<0.05);bureaucratic leadership style and job satisfaction(r = 0.15, p<0.05), autocratic leadership style and job satisfaction (r = - 0.04, p<0.05), laissez faire leadership style and job satisfaction (r = - 0.13, p<0.05). There were significant joint effects of the independent variables on job satisfaction of library personnel; (F(3,422) = 54.64; R= 0.53, p< 0.05). Variance of independent variables to job satisfaction was 28%. Each of the independent variables showed relative contributions to job satisfaction of library personnel thus: career progression (? = 0.42; t = 9.80; p< 0.05), work motivation (? = -.67, t = 5.39; p< 0.05) and leadership styles (? = 0.72; t = 6.36; p< 0.05). Further results showed positive correlations of career progression, work motivation and bureaucratic leadership style with job satisfaction and negative correlation of autocratic and laissez-faire leadership styles with job satisfaction. Career progression, work motivation, and bureaucratic leadership style enhanced job satisfaction of library personnel. Therefore, the Federal Civil Service should ensure stable career progression, and good work motivation for library personnel to improve their job satisfaction. In addition, bureaucratic leadership style of the library personnel should be sustained to promote check and balances in the Federal Civil Service of Nigeria